Pengembangan Aplikasi Berbasis Android Untuk Meningkatkan Kepatuhan Pasien Gagal Jantung Dalam Merawat Diri Di Rumah - I Kadek Yoga Darma Putra; Agi Putra Kharisma; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Heart failure patients can experience re-hospitalization caused by several factors, one of which is the recurrence of the disease suffered. This recurrence occurs due to patients with heart failure who do not comply in carrying out recommended activities such as not taking medication in accordance with the doctor's orders and not carrying out the recommended therapy. To improve the compliance of heart failure patients in caring for themselves at home, a reminder and education is needed for heart failure patients. The method used in this research is Waterfall software development method. This method was chosen because the functional needs of the system have been clearly defined from the beginning. In this study also used MVVM architecture and Clean Architecture. Tests conducted in this study include functional, usability and compatibility testing. Functional testing produces a 100% success percentage. In usability testing resulted in a success rate of 87.5% in test cases of heart failure patients and 100% in the case of health workers test. In addition, usability testing using the System Usability Scale (SUS) method produces a score that falls into the category of Good or Acceptable. The compatibility testing resulted in a good success scale of the overall device tested which has an android version with an API level of at least 21 (lollipop version 5.0).